Aerodynamic performance enhancement of centrifugal compressor using numerical techniques [version 1; peer review: 2 approved] - Srinivas G; Shivani S; Amar Murthy A (F1000Research)
Background Centrifugal compressors are dynamic machines utilizing a rotating impeller, efficiently accelerate incoming gases, transforming kinetic energy into pressure energy for compression. They serve a wide range of industries, including air conditioning, refrigeration, gas turbines, industrial processes, and applications such as air compression, gas transportation, and petrochemicals, demonstrating their versatility. Designing a centrifugal compressor poses challenges related to achieving high aerodynamic efficiency, surge and choke control, material selection, rotor dynamics, cavitation, erosion, and addressing environmental considerations while balancing costs. Optimizing maintenance, reliability, and energy efficiency are essential aspects of the design process. Methods The primary objective of this research is to comprehensively investigate and improve the aerodynamic performance of centrifugal compressors. To accomplish this, a comprehensive investigation of variables such as blade number and hub diameter, along with various turbulence models will be conducted. This approach will leverage numerical techniques to fill the significant gaps in the current literature regarding centrifugal compressor design and optimization. The study encompasses the evaluation of two turbulence models, namely Shear Stress Transport and K-epsilon. Furthermore, it delves into the fine-tuning of blade geometry, including variations in blade number and hub diameter, aiming to refine the design for optimal performance. Extensive analyses using Ansys CFX encompass key variables such as Pressure, Mach Number, Density, Velocity, Turbulence Kinetic Energy, and Temperature. Results Notably, the optimized pressure profile yielded remarkable results, achieving a substantial 36% improvement, demonstrating the tangible benefits of these design enhancements. Conclusion The outcomes of this research hold significant utility for engineers, manufacturers, and regulatory bodies, offering invaluable insights and guidance to enhance compressor performance and efficiency.